2004
DOI: 10.1158/1055-9965.epi-463-2
|View full text |Cite
|
Sign up to set email alerts
|

Current Research Promises and Challenges in Behavioral Oncology

Abstract: The Behavioral Oncology Interest Group of the American Society of Preventive Oncology held a Roundtable session on March 10, 2002, at the American Society of PreventiveOncology annual meeting in Bethesda, Maryland, to discuss the current state-of-the-science in behavioral approaches to cancer prevention and control and to delineate priorities for additional research. Four key areas were considered: (a) behavioral approaches to cancer genetic risk assessment and testing; (b) biological mechanisms of psychosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…73,83 However, there is a growing sense that the cognitive domain needs to be considered as one component of a larger constellation of interrelated disease-specific cognitions and affects. 34, 84 Effect sizes for such factors as risk perception appear comparatively small, 74 emotion variables have been shown to predict screening over and above cognitive variables, 34,85 and at least two studies have shown that worry mediated risk-screening relations. 86,87 …”
Section: Cognitive Variablesmentioning
confidence: 99%
“…73,83 However, there is a growing sense that the cognitive domain needs to be considered as one component of a larger constellation of interrelated disease-specific cognitions and affects. 34, 84 Effect sizes for such factors as risk perception appear comparatively small, 74 emotion variables have been shown to predict screening over and above cognitive variables, 34,85 and at least two studies have shown that worry mediated risk-screening relations. 86,87 …”
Section: Cognitive Variablesmentioning
confidence: 99%
“…Whereas many previous nutrition studies consisted of a single tailored message and sbort-term follow-up of 1 to 4 montbs (Brug, Campbell, & Van Assema, 1999;Brug et al, 1996;Campbell et al, 1994), this study compares groups with a single contact and groups witb four contacts over an 11-montb period, with final assessment at 12 montbs. Tbis design addresses an area of research (tbe relative efficacy of differing amounts of tailoring) recommended by tbe American Society of Preventive Oncology (Miller et al, 2004). Few nutrition studies have attempted to assess tbe value of retailoring or "iterative" tailoring as this one does, a question tbat could affect the cost of future interventions.…”
mentioning
confidence: 99%
“…There is increasing recognition that patients vary in key characteristics that impact decision making such as numeracy, 22,23 relative health stock, 24,25 age, 26 gender, [26][27][28] and other cognitive-affective variables. [29][30][31] Thus, a "1 size fits all" approach to communication will not promote the best decisions and the greatest satisfaction. 10,32 Efforts to improve physician-patient communication have included training of patients 33 and training of physicians.…”
Section: Discussionmentioning
confidence: 99%